Apaturinae (Lepidoptera: Nymphalidae) from the Korean Peninsula: Synonymic Lists and Keys to Tribes, Genera and Species - Lee, Young June (Zootaxa, 2009)
This paper provides keys to tribes, genera and species and synonymic lists for the 12 butterfly species belonging to eight genera of Apaturinae (Lepidoptera: Nymphalidae) from the Korean Peninsula: Apatura ilia (Denis and Schiffermüller), Apatura metis Freyer, Apatura iris (Linnaeus), Hestina japonica (Felder and Felder), Hestina assimilis (Linnaeus), Sasakia charonda (Hewitson), Mimathyma schrenckii (Ménétriès), Mimathyma nycteis (Ménétriès), Sephisa princeps (Fixsen), Chitoria ulupi (Doherty), Dilipa fenestra (Leech) and Dichorragia nesimachus (Doyère). Species accounts include brief summaries of each taxon’s biology, taxonomy and life history. The distributional ranges of the Hestina persimilis species complex are discussed and illustrated.